Applying microteaching to the training of movement explanation and demonstration skills of physical education majors: findings of a pilot study - Chai, Weili; Soh, Kim Geok; Abdullah, Borhannudin; Wang, Qingbo (Human Resource Management Academic Research Society, 2024)
This pilot study aimed to evaluate the effects of microteaching on the diagnosis and error correction skills of Chinese university students majoring in physical education, using a Cluster Randomised Controlled Trial (CRCT) design. Yancheng Teachers University served as the experimental group (microteaching training), and Huaiyin Normal University was the control group (standard training), with 54 participants aged 20-22. Experts reviewed and approved the training procedures. Data analysis used Generalised Estimation Equations (GEE) and Bonferroni tests. Significant improvements in the skills were observed within both experimental and control groups over time. At the pre-test stage, no significant differences were found between the groups. but at the post-test stage, the experimental group showed statistically significant improvements in the skills compared to the control group (DECS: Cohen's d = 3.75, p < 0.05). These results suggest that microteaching is more effective than standard training in enhancing diagnosis and error correction skills in physical education majors, making it a superior method for teaching skills training.